2020
DOI: 10.1016/j.radonc.2020.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Low dose radiation therapy for COVID-19: Effective dose and estimation of cancer risk

Abstract: Background and purpose The objective of this work is to evaluate the risk of carcinogenesis of low dose ionizing radiation therapy (LDRT), for treatment of immune-related pneumonia following COVID-19 infection, through the estimation of effective dose and the lifetime attributable risk of cancer (LAR). Material and methods LDRT treatment was planned in male and female computational phantoms. Equivalent doses in organs were estimated using both treatment planning system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…Treating Female patient with low dose radiotherapy (with a dose of 100 cGy), aged 50 years, risk of cancer induction is 40%. Therefore, based on this study, it is impossible to report that stochastic effects are insignificant for low dose radiation therapy for curing COVID-19, especially for young women 34 . However, United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) reported that radiogenic lung cancer is more in adult than children as adults more sensitive to LDRT therefore the correlation between age and radiogenic lung is not clear yet 35 .…”
Section: Risk Of Induced Cancer After Ldrtmentioning
confidence: 83%
“…Treating Female patient with low dose radiotherapy (with a dose of 100 cGy), aged 50 years, risk of cancer induction is 40%. Therefore, based on this study, it is impossible to report that stochastic effects are insignificant for low dose radiation therapy for curing COVID-19, especially for young women 34 . However, United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) reported that radiogenic lung cancer is more in adult than children as adults more sensitive to LDRT therefore the correlation between age and radiogenic lung is not clear yet 35 .…”
Section: Risk Of Induced Cancer After Ldrtmentioning
confidence: 83%
“…Although numerous data show that low dose radiotherapy may have anti-inflammatory properties, the evidence supporting the use of low dose radiotherapy to treat COVID-19 infection remains preliminary. This approach could potentially have a favorable cost/effectiveness ratio, for a subgroup of COVID-19 patients for whom there is most often no therapeutic alternative and in a context of lack of access to resuscitation platforms ( García-Hernández et al, 2020 ). A prerequisite for achieving successful development of this experimental treatment is to more accurately identify what population could get benefit, if any, from this treatment, and to better determine the optimal timing/dose/fractionation to achieve the best therapeutic index with satisfactory safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the age at the exposure as an important factor was not considered in the effective dose. Thus, the effective dose is not recommended for epidemiological evaluations (31), and in this study, we estimated the cancer risks as a radiation side effect for whole lung LDRT It was proposed that LDRT may induce anti-in ammatory effects and helps to reduce or prevent the cytokine storm (6,20). Historical reports suggest radiation doses between 0.35 and 0.5 Gy for lung LDRT as an optimal dose, and higher doses may induce excessive in ammation in pneumonia patients (32).…”
Section: Discussionmentioning
confidence: 99%